Marriage Registration Law Reformulation in Indonesia (Studi of Law and Regulations on Marriage) - Zainuddin, Asriadi; Jamil, Abdul; Sumanto, Dedi (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Marriage registration serves to create order in the administration of marriage in society as well as to ensure the upholding of the rights and obligations of husband and wife. This is a preventive state law policy to coordinate the community for the realization of order and order in the system of life, including in marital problems which are believed to be inseparable from various irregularities and disputes between husband and wife. Therefore, the involvement of the authorities/state in regulating marriage in the form of registration is a must.Purposes of the Research: The purpose of this study is to examine and analyze the formulation of legal substance regulation of marriage registration in Indonesia and to analyze and formulate the ideal concept of reformulation of marriage registration law in Indonesia.Methods of the Research: This research is a type of qualitative study that starts from the constructivism paradigm. The approach method used in this study is the socio-legal approach method (socio legal study). A study that examines law as a social fact that can be seen in the realm of experience as a pattern of behavior in the form of social institutions.Results of the Research: The reformulation concept offered by the author is to revise the sound of Article 2 paragraphs 1 and 2 which requires registration of marriages and contains criminal sanctions in it with the aim of providing a deterrent effect for perpetrators of underhand marriages. in the sense that this criminal sanction is used if the previous related sanctions are no longer powerless in the sense that this criminal sanction is a criminal sanction that is used after civil or administrative sanctions are applied.